2018
DOI: 10.1063/1.5010265
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN-based deep UV LEDs grown on sputtered and high temperature annealed AlN/sapphire

Abstract: The performance characteristics of AlGaN-based deep ultraviolet light emitting diodes (UV-LEDs) grown by metalorganic vapor phase epitaxy on sputtered and high temperature annealed AlN/sapphire templates are investigated and compared with LEDs grown on epitaxially laterally overgrown (ELO) AlN/sapphire. The structural and electro-optical properties of the devices on 350 nm sputtered and high temperature annealed AlN/sapphire show similar defect densities and output power levels as LEDs grown on low defect dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 184 publications
(113 citation statements)
references
References 21 publications
1
103
0
Order By: Relevance
“…Evidently, the crystallinity at a thickness of 600 nm was improved compared with that at 400 nm despite the cracking of the film, indicating that grain size was certainly increased by annealing, but that the film partially cracked through cooling down. Based on the relationship of (0001) [11][12][13][14][15][16][17][18][19][20] AlN || (001) [110] diamond confirmed by XRD, transmission electron microscope (TEM) and NBD at the AlN/diamond interface were performed as shown in Figure 5. [14] Therefore, the crystallinity of FFA sp-AlN/diamond structure can be further improved, e.g., by optimizing sputtering condition to prevent cracking at thick AlN.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Evidently, the crystallinity at a thickness of 600 nm was improved compared with that at 400 nm despite the cracking of the film, indicating that grain size was certainly increased by annealing, but that the film partially cracked through cooling down. Based on the relationship of (0001) [11][12][13][14][15][16][17][18][19][20] AlN || (001) [110] diamond confirmed by XRD, transmission electron microscope (TEM) and NBD at the AlN/diamond interface were performed as shown in Figure 5. [14] Therefore, the crystallinity of FFA sp-AlN/diamond structure can be further improved, e.g., by optimizing sputtering condition to prevent cracking at thick AlN.…”
Section: Resultsmentioning
confidence: 99%
“…XRD φ scans revealed that the conventional problem of the in-plane epitaxial relationship in hexagonal AlN/(001) diamond structure was stabilized in the single domain of (0001) [11][12][13][14][15][16][17][18][19][20] Crystallinity of the AlN film was significantly improved by the FFA, leading to the XRC-FWHM value of 1490 arcsec at FFA Sp-AlN thickness of 400 nm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations